Hubungan Kepatuhan Penggunaan Obat terhadap Tekanan darah dan Kualitas Hidup Peserta Prolanis Hipertensi di Kabupaten Demak - Galih Kurniawan; Ika Purwidyaningrum; Wiwin Herdwiani (Fakultas Farmasi Universitas Setia Budi, 2022)
Optimal quality of life for people with hypertension is very important so as not to reduce patient productivity. Adherence drug use is one of the factors thought to be associated with blood pressure and quality of life. This study aims to determine the relationship between adherence to medication use on blood pressure and quality of life of patients with hypertension in Prolanis . participants at the First Level Health Facility of the Klinik Pratama. This study used a cross sectional design involving hypertensive patients participating in Prolanis who met the inclusion and exclusion criteria at seven Primary Clinics in Demak Regency. Data on medication adherence were obtained using the MARS-5 questionnaire, quality of life data using the EQ-5D-5L questionnaire, and blood pressure data using a digital sphygmomanometer. The relationship between the level of compliance with blood pressure and the relationship between the level of compliance with quality of life was tested using Spearman rho analysis. The results of the study with a total of 87 respondents showed that most of them had moderate levels of adherence (52%), systolic blood pressure (64%) and diastolic blood pressure (57%) were not controlled and the average utility score was 0.845. There is a relationship between drug use adherence to systolic and diastolic blood pressure (P = 0.009), (P = 0.032) with a weak correlation level (r = 0.27), (r = 0.23) and there is a relationship between drug use adherence on quality of life (P = 0.000) with a moderate level of correlation (r = 0.42).